Hyaluronan – A Functional and Structural Sweet Spot in the Tissue Microenvironment - Monslow, James; Govindaraju, Priya; Puré, Ellen (Frontiers in Immunology, 2015)
Transition from homeostatic to reactive matrix remodeling is a fundamental adaptive tissue response to injury, inflammatory disease, fibrosis and cancer. Alterations in architecture, physical properties and matrix composition result in changes in biomechanical and biochemical cellular signaling. The dynamics of pericellular and extracellular matrices, including matrix protein, proteoglycan and glycosaminoglycan modification are continually emerging as essential regulatory mechanisms underlying cellular and tissue function. Nevertheless, the impact of matrix organization on inflammation and immunity in particular, and the consequent effects on tissue healing and disease outcome are arguably under-studied aspects of adaptive stress responses. Herein, we review how the predominant glycosaminoglycan hyaluronan (HA) contributes to the structure and function of the tissue microenvironment. Specifically, we examine the evidence of HA degradation and the generation of biologically-active smaller HA fragments in pathological settings in vivo. We discuss how HA fragments versus nascent HA via alternate receptor-mediated signaling influence inflammatory cell recruitment and differentiation, resident cell activation, as well as tumor growth, survival and metastasis. Finally, we discuss how HA fragmentation impacts restoration of normal tissue function and pathological outcomes in disease.